Relationship between Logistical Support Factors and Effective Contract Management in Royal Malaysian Navy - Muslim Diekola Akanmu; Ahmad Sarkawi Azizi; Mohamad Ghozali Hassan; Mustakim Melan (International Journal of Supply Chain Management, 2019)
This paper aimed to provide an insight on the effective contract management (ECM) relationship with logistical support factors namely financial support, leadership support, contract compliance, technological support and contracting officer competency within the logistic handling in Royal Malaysian Navy (RMN). The paper determined whether the logistical support factors have an impact on effective contract management in a maritime defense organization like RMN, in evidence of its readiness and agility in coping with any incoming threat. The paper used a literature search and comparative analysis complemented with examples from previous studies. No study has been done to explore aspects of skills and competency among RMN supply and secretariat officers, especially for those officers who are at the level of executives and professionals in the naval service. In conjunction with the regulatory requirements, risk management and cost control, many enterprises, organizations and firms are now taking stock of effective contract management in order to reduce uncertainty and enhance visibility and performance measure.